Monetary reform in the context of the post-war economic recovery of Ukraine: posing the question - Volodymyr Studinski; Galyna Studinska (Економічний вісник університету, 2023)
Formulation of the problem. The modern Russian-Ukrainian war, which began back in 2014 with the occupation of Crimea and parts of the Donetsk and Luhansk regions, as well as its subsequent continuation and deployment of a full-scale invasion of the territory of Ukraine by the Russian army, which led to serious destruction of the cities and villages of our country, set a number of serious issues not only in the context of the functioning of the country's economy, but also in the context of its post-war recovery. The issue of economic recovery of Ukraine is now being actively considered and studied both by our state and by partner countries. Reforming the monetary system of Ukraine in this context takes on special importance. The subject of research is the monetary system of Ukraine in historical dynamics. The purpose of this study is to determine possible prospects for reforming the modern monetary system of Ukraine in the post-war period. Also determination of prospects for integration of the monetary system of Ukraine into the monetary system of the EU. The methodological basis of the research is historical, analytical, comparative and statistical methods. Research results. In the article, an attempt is made to consider the issue of the perspective of the reform of the monetary system of Ukraine in the post-war period and to determine the orientations of its development in the future. Field of application. The results of the article can be used by universities, public and political organizations, students, graduate students, teachers; state administration bodies. Conclusions. As a result of the full-scale aggression of the Russian Federation against Ukraine, a number of serious problems arose in the field of finance. In particular, this concerns the monetary system of Ukraine. First of all, we are talking about stabilization of the national currency and control of inflationary processes. In the post-war period, the question of bringing the money and commodity mass into line, as well as the exchange rate of the national currency, the hryvnia, with other currencies of the world, will arise acutely.